(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Word formation plays a crucial role in the enrichment and expansion of a language’s vocabulary system. This article explores the various types of word formation processes, including affixation, compounding, conversion, clipping, blending, acronym, borrowing, back-formation, reduplication, and neologism. Each process contributes to the dynamic evolution of language by creating new lexical units, adapting existing words, and facilitating communication in an ever-changing linguistic landscape. By analyzing these processes, the study highlights their significance in vocabulary development and linguistic innovation. The findings suggest that word formation not only enhances linguistic expressiveness but also reflects cultural and technological advancements.